TI_GERICHTE 30.2005.6 vom 7. November 2005 , Ripetuta attività svolta da un grafico per il medesimo cliente ritenuta indipendente. - TI Tribunale d'appello (2005)
Ripetuta attività svolta da un grafico per il medesimo cliente ritenuta indipendente.